Biochemical Characterization of Early Osteoarthritis in the Ankle. (13th February 2014) - Schmal, Hagen; Salzmann, Gian M.; Langenmair, Elia R.; Henkelmann, Ralf; Südkamp, Norbert P.; Niemeyer, Philipp
Abstract : Purpose. Reliable data about in vivo regulation of cytokines in early ankle osteoarthritis (OA) are still missing. Methods. 49 patients with a mean age of 33 ± 14 years undergoing an arthroscopy of the ankle with different stages of chronic OA were prospectively included in a clinical trial. Lavage fluids were analyzed by ELISA. Additionally, clinical parameters and scores (FFI, CFSS, and AOFAS) were evaluated and supplemented by the Kellgren Lawrence Score (KLS) and the ankle osteoarthritis scoring system (AOSS). Results. ICRS grading of cartilage damage, previous operations, and duration of complains were strong indicators for OA progress and showed correlations to age, clinical scores, validated KLS, and AOSS (P < 0.04 ). Systemic and intraarticular inflammatory parameters were low in all patients. Biochemically, aggrecan and BMP-7 positively indicated OA with statistically significant associations with duration of symptoms, FFI, AOFAS, and KLS (P < 0.04 ). In contrast, BMP-2 levels showed statistically significant negative correlations to aggrecan or BMP-7 concentrations, which is in line with the negative association with ICRS score and KLS and the positive correlation with FFI (P < 0.03 ). Conclusions. We were able to identify different key markers of OA in the ankle as aggrecan, BMP-7, and BMP-2, offering starting points for new ways in diagnostics and interventional strategies.